Reconditioning of motor transport (questionnaire) (1937)
036-0046-001 VOLUNTARY INDUSTRIAL AID FOR SPAIN TELEPHONE: HOLBORN 6119 32, GREAT ORMOND STREET LONDON, W.C.1 1937 ADVISORY COMMITTEE: HARRY ADAMS, Chairman (Amalgamated Union of Building Trade Workers) ALFRED BARNES, M.P. (Chairman of the Co-operative Party) A.C. BASSEBE (Hydraulic Coupling Co., Ltd.) H.G. BROTHERTON (Sheet Metal Workers Union) A.W. COSTER Electrical Trades Union) J. DUNNAGE. A.M. Inst., T. J. DAGGER (Amalgamated Society of Woodcutting Machinists) LORD FARINGDON BERT JOY (Amalgamated Society of Woodworkers) GEOFFREY PYKE, Hon. Secretary J. REEVES (Royal Arsenal Co-operative Society) JOE SCOTT, Treasurer (Amalgamated Engineering Union) J.R. SHANLEY (Amalgamated Union of Upholsterers) JACK TANNER (Amalgamated Engineering Union) Councillor D.C. WEBSTER, L.C.C. (National Union of Vehicle Builders) A.M. WALL (London Trades Council) R. H. EDWARD (National Union of Vehicle Builders) RECONDITIONING OF MOTOR TRANSPORT INFORMATION QUESTIONNAIRE Please fill in:- (1) Are you prepared to give labour services? (2) What days are most suitable for you? How many hours: from what time to what time? Mondays from ............to............. Tuesdays from............to............. Wednesdays from ............to............. Thursdays from ............to............. Fridays from ............to............. Saturdays from ............to............. Sundays from ............to............ 3. What section of the work are you prepared to do? 4. What area would you prefer to work in? SIGNED ADDRESS 292/946/36/46